The archaeology of knowledge and the discourse on language - Foucault, Michel 1926-1984 (New York Pantheon Books, 1972)
Madness, sexuality, power, knowledge-are these facts of life or simply parts of speech? In a series of works of astonishing brilliance, historian Michel Foucault excavated the hidden assumptions that govern the way we live and the way we think. The Archaeology of Knowledge begins at the level of 'things said' and moves quickly to illuminate the connections between knowledge, language, and action in a style at once profound and personal.